Toxoplasmosis in Southern Africa - Jacobs, Michael Roy (My University, 2015)
Since its discovery in 1908, the protozoan Toxoplasma gondii has been found to be one of the most versatile and prolific of all parasites. Infections with T. gondii have been reported from most parts of the world in humans, animals and birds. Toxoplasma has recently been shown to be a coccidian, which has developed from a one-host to a twohost cycle. The definitive hosts are felines, in whose gastro-intestinal tracts the isosporan phase of development takes place. The toxoplasmic phase occurs in many organs of other animal and bird hosts. Transmission occurs via ingestion of oocysts shed by cats or cysts contained in raw or inadequately cooked meat, particularly mutton and pork. Infections in humane occur at rates of up to 6% oer year or higher. The major complication of infection is congenital transmission if acute infection occurs during pregnancy. Maternal infection rates of 10 to 115 per 10 000 pregnancies occur in different parts of the world, witi up to 40% of such infections resulting in congenital infections. Fortunately, only about 15% of foetal infections are severe and 20% mild, with the remainder being asymptomatic. The prevalence of toxoplasmosis varies in different parts of the world, being highest in hrC humid climates and lowest in cold or arid climates. In Southern Africa, the overall prevalence found in these studies was 21%, varying from 30% in Natal to 10% in the Orange Free State. Prevalence varied with ethnic group, from 9% in the San (Bushmen) of South West Africa and Botswana to 28% in Coloureds and Indians. Prevalence ir. Whites was lower than in other ethnic groups in South Africa. The annual incidence of toxoplasmosis in Southern Africa is about 1% up to the age of 25 years, falling thereafter to 0.5%. The incidence of toxoplasmosis during pregnancy was studied, and 20 acu.e infections were detected in 6705 pregnancies (0.03%) in 3 Johannesburg hospitals. Congenital transmission occurred in 2 of these 20 patients, and resulted In 1 severely affected and 1 asymptomatic infant. This congenital transmission rate of 10% is low compared to up to 40% found in other countries. Transmission of toxoplasmosis in Southern Africa appears to involve both cysts and oocysts, although oocysts appear to be more important in the younger age groups. Virulence and congenital transmission rates are low. The estimated number of maternal infections in South Africa is 2 500 per year, resulting in 250 congenital infections. Thirty-eight of these congenitally infected babies would have severe infection, 48 mild infection and 165 would be asymptomatic. If toxoplasmosis could be prevented, 1 to 2 severe infections per 16 500 births could be avoided. Unfortunately, there are at present no measures such as immunization available, and the only control measures advocated are the avoidance of sources of cyste (raw meat) and oocysts (soil contaminated with cat faeces) during pregnancy. Screening programmes for the detection of acute toxoplasmosis during pregnancy would be very difficult and expensive to undertake, and there are many far more important diseases which should receive public health priority. Fortunately, the incidence of toxoplasmosis during pregnancy and the congenital transmission rate are particularly low by world standards. Until vaccination or other practicable preventive measures are developed, little can be dor to prevent or treat toxoplasmosis during pregnancy.
A Thesis Submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg for the Degree of Doctor of Philosophy in Medicine Johannesburg 1978